Factors Influencing Inflation: Insights from the Nepalese Economy - Santosh Khanal; Shantosh Paudel (Tribhuvan Journal, 2024)
Inflation is a persistent issue in developing nations such as Nepal, resulting in serious economic and social consequences. This article examines the macroeconomic determinants of inflation in Nepal, considering the variables as government expenditure, exchange rate remittances, real GDP, and the consumer price index of India. Using the time series data from 1975 to 2023. It employs the Engel-Granger two-step cointegration test to examine the short- and long-term causal connections between Nepal's consumer price index (inflation) and all of these variables. The augmented Dickey-Fuller unit root test confirms that the variables are stationary at first difference, suggesting they possess an integrated order of I. The Engel-Granger test established that there is co-integration among the variables. Additionally, the error correction term (ECT) was found to be statistically significant, with a negative coefficient. The causal association between the selected dependent and explanatory variables in Nepal is both significant and persistent. The empirical findings suggest that India's inflation highly affects inflation in Nepal. Furthermore, the enduring effects of broad money supply and government expenditure are also substantial factors. The results indicate an inverse relationship between inflation and real GDP in Nepal, whereas remittances have no significant impact on consumer prices in the nation. So, it is vital to control inflation to be able to deal with poverty and economic growth. Policies are needed to keep the inflation target range around the optimum inflation rate to accelerate the pace of economic growth and ensure that the adverse effect inflation has on economic growth is minimized.